Facile synthesis of magnetic Fe@Al-ZnO nanocomposite for photocatalytic bacterial inactivation under visible-light irradiation. (1st March 2021) - Peng, Ziling; Li, Yang; Wang, Wei; Li, Xiang; Lv, Xingdong; Chen, Xia; Shi, Yan; Zhou, Shihua
Abstract: Magnetic Fe@Al-ZnO nanocomposite was systhesized through a facile two-step precipitation process for the first time, and employed as a highly active photocatalyst for visible-light-driven (VLD) inactivation of Escherichia coli . The as-synthesized nanocomposite was analyzed using X-ray diffraction (XRD), Brunauer-Emmett-Teller (BET), scanning electron microscope (SEM), vibrating sample magnetometer (VSM), X-ray photoelectron spectroscopy (XPS), UV–vis diffused reflectance spectra (UV–vis DRS) and photoluminescence (PL) spectra. The Fe@Al-ZnO photocatalysts displayed typical ferromagnetic property with the saturation magnetization of 35.2 emu/g, which predominantly facilitated magnetic separation and recycling in applications. The photocatalyst dosage was found to have a significant influence on the VLD photocatalytic bacterial inactivation activity of Fe@Al-ZnO. Under visible-light irradiation, 40 mg of Fe@Al-ZnO could entirely inactivate 7-log of bacterial cells in 5 h. Notably, the phase structure and magnetic property of the nanocomposite after photocatalysis exhibited almost no evident change compared with that before photocatalysis, indicating excellent stability of Fe@Al-ZnO photocatalyst. Due to the privileges of facile preparation, relatively low cost, powerful photocatalytic efficiency, excellent stability as well as magnetic recovery property, Fe@Al-ZnO nanocomposite was anticipated to possess remarkable potential in VLD photocatalytic inactivation of bacteria. Highlights: Fe@Al-ZnO was prepared by a facile two-step precipitation method. Fe@Al-ZnO showed high photocatalytic activity under visible-light irradiation. Fe@Al-ZnO had excellent stability for photocatalytic bacterial inactivation. Fe@Al-ZnO could be easily collected from the reaction solution by a magnet. The doping of Al 3+ into ZnO in Fe@Al-ZnO inhibited the photocorrosion of ZnO.